A TEST OF GENERAL STRAIN THEORY: EXPLORING GENDER SPECIFIC EMOTIONAL AND BEHAVIORAL VARIATION - Puckett, Sarah Rae (2008)
Traditional sociological theories examining delinquency typically were formulated to explain male behavior. With the universal recognition of the crime-gender gap, it is important to determine the applicability of these theories to female delinquency. This research uses the National Survey of Children (1981) to test propositions from general strain theory, specifically those outlined by Broidy and Agnew (1997). The data set allows for an expansion of the types of strain and delinquency typically examined in strain tests. Ordinary least squares regression, path analysis and a series of t-tests were used to determine variations in male and female emotional and behavioral responses to strain. The results of this analysis suggest that certain types of strain influence which type of delinquency males and females will pursue and that the intervening effect of negative emotion are consequential for both genders. Suggestions for future research are also discussed